The Regulatory Effect of the Kinase Inhibitor PD98059 on Autophagic Flux During Trypsinogen Activation in Pancreatic Acinar Cells. Issue 2 (February 2020) - Yao, Wenchao; Zhu, Defu; Lu, Haifeng; Liu, Chao; Sun, Bei; Zhang, Weihui; Xue, Dongbo
Abstract : Objectives: To study the role of kinase inhibitor PD98059 on autophagy flow in the process of trypsinogen activation in pancreatic acinar cell and its related mechanism. Methods: In the present study, bioinformatics analysis was used to predict kinases and their most relevant inhibitor (PD98059) which participates in autophagy of acute pancreatitis (AP). The rat pancreatic acini AR42J cells were divided into 4 groups: control group, sodium taurocholate hydrate (TLC) group, PD98059 group, and TLC + PD group. Twenty-seven Sprague-Dawley rats were divided into 3 groups (n = 9), including control group, severe AP (SAP) group, and SAP + PD group. We detected trypsinogen activation, autophagic activation, lysosome pH, and cathepsin-L activity in vivo and in vitro. Results: Results revealed trypsinogen activation was significantly inhibited in mitogen-activated protein kinase 1, JAK2, LYN, and their common inhibitor was PD98059. The trypsinogen activation, Beclin1, and light chain 3 II expressions were reduced, whereas the expressions of lysosomal-associated membrane protein 2, cathepsin L1, and cathepsin-L activity is upregulated after the PD98059 pretreatment, both in vivo and in vitro. Conclusions: Lysosomal dysfunction blocked autophagy flux, accompanied by increasing pancreatic acinar cell autophagy in the process of trypsinogen activation. PD98059 inhibited AP occurrence and pancreatic injury via improving the blocked autophagic pathway and reducing trypsinogen activation. Abstract : Supplemental digital content is available in the text.